The Need to Strengthen Ideological Immunity in Young People in the Process of Globalization - Matluba Mavarovna Yuldasheva (Genius Journals, 2023)
The article focuses on the laws of thought, logical thinking, logical consistency and common features of human thinking, and the study of the first stage of the science of logic.
Keywords: Thought; rationality; thinking; event